THE INFLUENCE OF GENDER ON SPEAKING ANXIETY IN ENGLISH CLASSES AT POLITEKNIK NEGERI CILACAP: A MIXED-METHODS STUDY AND PEDAGOGICAL IMPLICATIONS - Annisa Romadloni; Laura Sari; Linda Perdana Wati (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2025)
Abstract Speaking anxiety serves as a significant barrier to oral proficiency in English for Specific Purposes (ESP) courses. Yet, the influence of gender on this affective factor within Indonesian vocational education remains underexplored. This mixed-methods study investigated speaking anxiety patterns at Politeknik Negeri Cilacap. Data were collected from 90 students (45 male, 45 female) using a modified FLCAS questionnaire,written reflections, and classroom observations, complemented by in-depth interviews with twelve selected participants. Although aggregate anxiety scores did not differ significantly between genders, item-level analysis revealed distinct differences. Female students reported significantly higher anxiety when called upon without preparation (cold calls), when fearing negative evaluation, and when speaking before the whole class. At the same time, both genders experienced comparable anxiety levels during formal presentations. Qualitative data confirmed that the fear of making mistakes, sensitivity to lecturer and peer judgment, and a lack of preparation time were the primary drivers of these patterns. Based on these findings, the research advocates for the implementation of gender-responsive scaffolding. Suggested pedagogical strategies include providing structured